2020
DOI: 10.1002/gps.5382
|View full text |Cite
|
Sign up to set email alerts
|

Catatonia in elderly psychiatric inpatients is not always associated with intense anxiety: Factor analysis and correlation with psychopathology

Abstract: Objective: Catatonic stupor has been linked to extreme fear. Whether the underlying phenomenology of every catatonic dimension is intense anxiety or fear remains unknown. Methods: One hundred and six patients aged ≥64 years were assessed for catatonia and clinical variables during the first 24 hours of admission. Two-sample t test were used to test for group differences. A principal component analysis was developed. Analysis of variance was performed to assess for differences in the diagnostic groups. Correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Nevertheless, it has also been postulated that it is possible to differentiate between emotive and nonemotive subtypes of catatonia, suggesting that not all catatonia patients experience emotional distress[ 26 ]. This theory seems to be supported by the findings that catatonia in older adults is not always related to intense anxiety[ 27 ].…”
Section: Resultsmentioning
confidence: 84%
“…Nevertheless, it has also been postulated that it is possible to differentiate between emotive and nonemotive subtypes of catatonia, suggesting that not all catatonia patients experience emotional distress[ 26 ]. This theory seems to be supported by the findings that catatonia in older adults is not always related to intense anxiety[ 27 ].…”
Section: Resultsmentioning
confidence: 84%
“…The thought is that catatonia could be an end state response to the feelings of imminent doom [ 21 ]. A study in an elderly population found that catatonic patients experienced more anxiety and hyperactivity [ 22 ]. This also may lend credibility to the notion that anxiety and fear can be part of the causes of catatonia, although catatonia is more complex and has more probable causes.…”
Section: Catatonia Causes Presentation and Pathophysiologymentioning
confidence: 99%
“…In terms of the objective psychopathology, some previous studies have endeavoured to apply principal component analysis to elucidate the structure of what is often displayed as a long list of rather disparate catatonic clinical signs ( 4 10 ). Sample sizes have varied between 106 and 2,703 and all have been in a mixed clinical population of patients with and without a diagnosis of catatonia.…”
Section: Introductionmentioning
confidence: 99%
“…These analyses have reduced the structure of catatonic signs to between two and six factors; this was often based on selecting factors with an eigenvalue greater than 1, but the method of model selection was not always clear. Models with fewer factors have tended to distinguish positive and negative (or hyperkinetic and hypokinetic) signs with or without a factor for qualitatively abnormal movements ( 4 7 ). Models with more factors have been more varied, including components such as excitement or agitation, volitional disturbance, abnormal movements, inhibition, automatic movements, repetitive movements or echophenomena, grimacing and autonomic disturbance ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation